Misleading estimates of economic impacts of biological invasions: Including the costs but not the benefits - Boltovskoy, Demetrio (2022)
The economic costs of non-indigenous species (NIS) are a key factor for the allocation of efforts and resources to eradicate or control baneful invasions. Their assessments are challenging, but most suffer from major flaws. Among the most important are the following: (1) the inclusion of actual damage costs together with various ancillary expenditures which may or may not be indicative of the real economic damage due to NIS; (2) the inclusion of the costs of unnecessary or counterproductive control initiatives; (3) the inclusion of controversial NIS-related costs whose economic impacts are questionable; (4) the assessment of the negative impacts only, ignoring the positive ones that most NIS have on the economy, either directly or through their ecosystem services. Such estimates necessarily arrive at negative and often highly inflated values, do not reflect the net damage and economic losses due to NIS, and can significantly misguide management and resource allocation decisions. We recommend an approach based on holistic costs and benefits that are assessed using likely scenarios and their counter-factual.